2016
DOI: 10.1016/j.memsci.2015.09.024
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of hydrophobic flat sheet and hollow fiber membranes from PVDF and PVDF-CTFE for membrane distillation

Abstract: a b s t r a c tHydrophobic polyvinylidene fluoride (PVDF) membranes have been used in membrane distillation, however its performance in terms of permeation flux and salt rejection still needs to be improved. In this study, polyvinylidenedifluoride-co-chlorotrifluoroethylene (PVDF-CTFE), a PVDF based copolymer, was employed to fabricate both flat sheet and hollow fiber membranes. Two pore forming additives (PEG and LiCl) were used in order to examine their effects on the membrane micro-structure and consequentl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 73 publications
(38 citation statements)
references
References 35 publications
3
35
0
Order By: Relevance
“…Meanwhile, the particulate packed pore structure with high interconnectivity was shown. Similar morphology was reported in our previous work, in which a comparison between hydrophobic membranes by PVDF and PVDF-CTFE was conducted with/without additives [27]. In that work, it also demonstrated that the S-L demixing process showed more influence when additives was added as compared to the membrane without additives.…”
Section: Membrane Morphology Of M5supporting
confidence: 88%
See 2 more Smart Citations
“…Meanwhile, the particulate packed pore structure with high interconnectivity was shown. Similar morphology was reported in our previous work, in which a comparison between hydrophobic membranes by PVDF and PVDF-CTFE was conducted with/without additives [27]. In that work, it also demonstrated that the S-L demixing process showed more influence when additives was added as compared to the membrane without additives.…”
Section: Membrane Morphology Of M5supporting
confidence: 88%
“…1, which was same as the previous work [27] by adding a computer automatic recording unit. A super thermostat bath and a cryostat were used for temperature controlling.…”
Section: Direct Contact Membrane Distillation (Dcmd) Testmentioning
confidence: 99%
See 1 more Smart Citation
“…In the MD process, a hydrophobic microporous membrane is required, which acts as the separation medium. Currently, hydrophobic microporous membranes have been successfully prepared by the vacuum MD (VMD) process, and these include polyvinylidene fluoride (PVDF), polypropylene (PP) and polytetrafluoroethylene (PTFE), as well as PVDF copolymers such as polyvinylidene fluoride‐co‐hexafluoropropylene (PVDF‐HFP) and PVDF‐co‐trifluorochloroethylene (PVDF‐CTFE) . Of these, PVDF membranes are frequently used as hydrophobic separation membranes for MD because of their excellent hydrophobicity, chemical resistance and membrane‐forming processability.…”
Section: Introductionmentioning
confidence: 99%
“…All membranes showed open porous structure with crystals in the surface, which presented a similar microstructure as the lotus leaf (for M1−M6) and the electrospun nanofiber membrane (for M7− M9), because PVDF-CTFE has a higher crystallization tendency as confirmed in our previous work. 44 The crystals and particles aggregate pore structure became more significant as the exposure duration increased especially as can be found in the inserted images in Figure 2. The membrane 3-D surface morphology and membrane surface depth distribution image recorded by AFM are presented in Figure 3 and Figure S2, respectively.…”
Section: ■ Results and Discussionmentioning
confidence: 84%